Religiosity and Audit Judgment: The Mediating Effect of Moral Reasoning - Andreani Hanjani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examined the effect of religiosity on audit judgment and analyzes the mediating role of moral reasoning in this relationship. Primary data was collected from 51 auditors working at a Public Accounting Firm (KAP) in Yogyakarta through a questionnaire survey. The data were then analyzed using SPSS through multiple regression and mediation analysis to test the research hypotheses. The results show that religiosity has no significant effect on audit judgment, indicating that auditors' religious values ​​do not directly determine the quality of audit judgments. However, religiosity is proven to have a positive and significant effect on moral reasoning, while moral reasoning has a positive and significant effect on audit judgment. The research results also show that moral reasoning plays a role as a full mediation variable in the relationship between religiosity and audit judgment. Theoretically, this study strengthens Moral Development Theory by demonstrating that the influence of individual values ​​on professional decisions occurs through the process of moral reasoning. Practically, the results indicate the importance of developing moral reasoning through ethics education, professional training, and case-based learning to improve the quality of auditor decisions.